The Role of the National Unity and Politics Agency in the Supervision of Civil Society Organizations in Pandeglang Regency - Mohamad Yusup; Muhammad Jafar; Siti Herika Nopianti (ijd-demos, 2025)
Civil society organizations serve as government partners in supporting development and community empowerment. However, the implementation of oversight in Pandeglang Regency still faces various obstacles, such as irregular administrative reporting, failure to report changes in organizational leadership and secretariats, and suboptimal supervision by the National Unity and Politics Agency (Kesbangpol). This study aims to analyze the role of Kesbangpol in the oversight of civil society organizations and to identify the factors supporting and hindering its implementation. The study employs a qualitative method with a descriptive approach. Data were collected through interviews, observation, and documentation, and subsequently analyzed using the Miles and Huberman model. The research utilizes role theory as proposed by Biddle and Thomas (cited in Sarwono, 2015) and supervision theory by Situmorang (1994). The results indicate that the Pandeglang Regency Kesbangpol has conducted oversight through outreach (socialization), guidance, administrative checks, document verification, monitoring, evaluation, and coordination with relevant agencies. However, implementation remains suboptimal because some civil society organizations have not fulfilled administrative obligations, failed to report changes in leadership and secretariats, and have not all received direct guidance. Supporting factors include a clear legal basis, inter-agency coordination, the provision of guidance, and the commitment of agency personnel. Meanwhile, inhibiting factors include limited human resources and budget, the vastness of the territory, the large number of civil society organizations, and low levels of compliance and administrative literacy. Therefore, strengthening guidance, coordination, outreach, and human resource capacity is essential to ensure more effective oversight of civil society organizations. Keywords: Role, Oversight, Civil Society Organizations, National Unity and Politics Agency.